Mengurai kontribusi perempuan dalam ekonomi kreatif: Menelusuri jejak kreativitas dan keberlanjutan - Prista, Alexchandra Nurfadila (Maliki Interdisciplinary Journal, 2024)
This article examines the role of women in the creative economy in Indonesia and its impact on economic sustainability. Women face challenges such as pay gaps, gender stereotypes, and limited access to education, but have great potential in creative sectors such as fashion, art, and technology. Empowering women through the creative economy can encourage innovation and inclusive and sustainable economic growth. Examples of success and initiatives such as the Malang Creative Center show real efforts to support the role of women. Overcoming structural and cultural barriers and increasing access to resources are important steps to maximize women’s contribution to the creative economy.